Multifractal behavior of an air pollutant time series and the relevance to the predictability. (March 2017) - Dong, Qingli; Wang, Yong; Li, Peizhi
Abstracts: Compared with the traditional method of detrended fluctuation analysis, which is used to characterize fractal scaling properties and long-range correlations, this research provides new insight into the multifractality and predictability of a nonstationary air pollutant time series using the methods of spectral analysis and multifractal detrended fluctuation analysis. First, the existence of a significant power-law behavior and long-range correlations for such series are verified. Then, by employing shuffling and surrogating procedures and estimating the scaling exponents, the major source of multifractality in these pollutant series is found to be the fat-tailed probability density function. Long-range correlations also partly contribute to the multifractal features. The relationship between the predictability of the pollutant time series and their multifractal nature is then investigated with extended analyses from the quantitative perspective, and it is found that the contribution of the multifractal strength of long-range correlations to the overall multifractal strength can affect the predictability of a pollutant series in a specific region to some extent. The findings of this comprehensive study can help to better understand the mechanisms governing the dynamics of air pollutant series and aid in performing better meteorological assessment and management. Graphical abstract: Highlights: Multifractal properties of nonstationary air pollutants records are investigated. The fat tailed probability density function is the major source of multifractality. The predictability is related to the proportion of multifractal strength. These findings can help perform better meteorological assessment and management.